Organizational capitalism: a look at the quality of labor life in university teaching staff - Terán Rosero, Ana Celina; Botero Álvarez, Carla Cristina (Cuadernos de Administración, 2011)
The experience of the international project on the theory of Organizational Capitalism as Psychosocial Risk Factor, KOFARIPS, applied in some Latin American educational institutions, evidences the concern of academics regarding the disequilibrium between labor and family actions generating tensions reflected in the quality of labor life of the teaching staff with possible bio-psychosocial consequences. Herein, we analyze some characteristics of the processes of subjectification of the theory, within the context of flexible reorganization of work from a comparative case study applied to sampling of professors from a public and a private university in Medellín, Colombia, related to the quality of labor life that includes four phases: perceptions of the work environment, experiences and sense of work, psychological wellbeing and impacts perceived, strategies and practices of individual and collective coping with organizational demands. The objective and subjective dimensions are considered, in addition to practices of professor resistance against the university-industry model, remuneration and the status of professors in universities, labor flexibility, entrepreneurship of public services, and the colonization of universities by the culture of organizational capitalism. Finally, we propose, through the analysis of the results, some alternatives of intervention to recover the true leading role of the professor and the onset of possible studies on the topic.